The Dialectics of Child Marriage and the Age of Maturity for Marriage: A Qur'anic Exegesis - Abd. Holik; Moch. Nurcholis (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
This article aims to analyze the gaps in the study of child marriage from a specific Qur'anic perspective. The primary focus of this study centers on the issue of the concept of marriage maturity in the Qur'an. The central problems addressed involve the practice of child marriage as portrayed in the Qur'anic context and the positioning of marriage maturity during the stage of maturity as per the Qur'an's perspective. To conduct this research, descriptive research methods were employed. This paper aims to delineate child marriage within the Qur'anic context and explore the stages of maturity by examining key phrases related to the concept of maturity found in various Qur'anic verses. The key phrases under consideration include